A percepção de magistrados e administradores judiciais sobre a atuação do contador em processos de recuperação judicial e falência - Hahn, Roberto Carlos (Universidade do Vale do Rio dos Sinos, 2018)
The companies recovery instituted by the Law 11.101/2005 presents many accounting aspects, pointing to the possibility for accountants to act as judicial administrators and/or expert accountant in these actions. In this regard, this study aimed to describe the perception of judges and judicial administrators about the performance of accountants in judicial actions involving bankruptcy and judicial recovery. A revision in literature was performed, considering the studies who approached the theme in a similar form to the proposed form adopted to this study, characterizing the activities of the expert accountant and. mainly. the judicial administrator to their accounting activities in judicial recovery and bankruptcy. The developed research was characterized as a field research using semi structured interviews and the sample had 8 (eight) interviewed, being 5 (five) judges and 3 (three) judicial administrators, being characterized as a convenience sample, obtained by accessibility criteria. The interviews’ results from the judges and judicial administrators revealed that accountants are able to perform with quality various tasks attributed to judicial administrators, although there is a sign in the sense that they need to improve the specific legal knowledge in judicial recovery and bankruptcy processes.
Keywords: Recuperação judicial; Falência; Administrador judicial; Contador; Perito contador; Legal reorganization; Bankruptcy; Legal administrator; Accountant; Accountant expert; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis